Aktivitas Vermisida Ekstrak Daun Miana Terhadap Ascaris Lumbricoides dengan Metode Real Time - Pakadang, Sesilia Rante; Ratnah, St.; Salasa, Alfrida Monica; Karim, Djuniasti (Media Farmasi, 2023)
Soiled Transmitted Helminth (STH) is an infectious disease caused by earthworms. The type of worm identified as the cause of STH is dominated by Ascaris lumbricoides and 3 other types. Many studies have been carried out to monitor the results of worm death. This study aimed to determine the profile of vermicides including onset of action, duration, and effectiveness of miana leaf extract compared to the drug pyrantel pamoat. The research method is to gradually start preparing miana leaf extract using a maceration process with continuous stirring, preparing the extract, and treating worms. The worms are placed in a sterile cup, then the test material is added and observed every hour. Worm death profiles such as paralysis, death, and life were observed for each worm subject. The results showed the death profile of worms after administration of miana leaf extract concentrations of 10, 20, and 40 mg/ml and pyrantel pamoat 2.5 mg/ml gave onset of action data for 4, 3, 2, and 1 hour respectively. The working duration of the test material is 5, 5, 3, and 1 hour respectively.  The effective dose is generated by a concentration of 40 mg/ml which can kill worms starting 2 hours after administration of the test material, with a duration of 1 hour  Soiled Transmitted Helminth (STH) adalah salah satu penyakit infeksi akibat cacing tanah. Jenis cacing yang teridentifikasi sebagai penyebab STH didominasi oleh Ascaris lumbricoides dan 3 jenis lainnya, penelitian telah banyak dilakukan dengan memantau hasil akhir kematian cacing. Tujuan penelitian ini mengetahui profil vermisida meliputi onset of action, durasi dan efektivitas ekstrak daun miana yang dibandingkan dengan obat pyrantel pamoat. Metode penelitian secara bertahap mulai penyiapan ekstrak daun miana dengan proses maserasi dengan pengadukan kontinu, penyiapan ekstrak dan perlakuan terhadap cacing. Cacing dimasukkan dalam cawan steril, kemudian ditambahkan bahan uji dan diamati setiap jam. Profil kematian cacing seperti paralisis, mati dan hidup diamati setiap subyek cacing. Hasil penelitian menunjukkan profil kematian cacing setelah pemberian ekstrak daun miana konsentrasi 10, 20 dan 40 mg/ml dan pyrantel pamoat 2,5 mg/ml memberikan data onset of action berturut 4, 3, 2 dan 1 jam. Durasi kerja bahan uji berturut 5, 5, 3 dan 1 jam. Dosis efektif dihasilkan oleh konsentrasi 40 mg/ml yang dapat mematikan cacing mulai 2 jam setelah pemberian bahan uji, durasi 1 jam.